Mortality Profile of Autopsied Geriatric Population: A Retrospective Study from Eastern India - Bhuyan, BR; Hansda, MK; Swain, R; Sahu , G; A, Naveen (Journal of Indian Academy of Forensic Medicine, 2024)
The elderly or geriatric age group is more vulnerable not only to natural diseases but also to accidents, suicides, and homicides in developing countries. To study the epidemiology, age, sex, cause and manner of elderly who were brought for medicolegal autopsy, this retrospective review analysed post-mortem reports of the elderly age group (60 years and above), who were referred for medicolegal autopsy at SCB Medical College & Hospital, Cuttack, Odisha between January 1, 2018, to December 31, 2019. The elderly individuals accounted for 12.6% of autopsies during the study period and most of them belonged to the 60-64 year age group and showed male predominance (72.2%). Overall, craniocerebral injuries (32.7%) were found to be the leading cause of death in the autopsied geriatric population, followed by poisoning (21%, n=160). Among natural causes, non-communicable diseases such as cerebrovascular accidents (3.4%) and cardiovascular diseases(2.6%) were the chief cause of death than communicable diseases such as tuberculosis (0.3%). Regarding manner, accidents were more frequently reported than suicides, natural deaths, and homicides. Of note, suicides were twice as common in elderly females (n=127) than in elderly males (n=63). The results of the study highlight that accidents represented significant deaths among the autopsied elderly age group than suicides, homicides, and natural diseases in India. Medicolegal autopsies play a paramount role not only in the determination of the cause and manner of such deaths but also in providing mortality statistics for effective policymaking.
Keywords: Geriatric deaths; Accidents; Gerontology; Medicolegal autopsy; Poisoning; Suicide